التسويق الشبكي: أحكامه الفقهية وآثاره الاقتصادية على الأفراد والدول - حواس، الهادى; جراية، عماد; هلال، عبدالحفيظ (جامعة الوادي - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2020)
هذا البحث الموسوم ب: التسويق الشبكي. أحكامه الفقهية وآثاره الاقتصادية على الأفراد والدول. كان الباعث إليه كثرة رواجه بين جميع أفراد مجتمعنا، وخاصة طبقة الشباب؛ لأن مما يملأ النفس سروراً، ويشرح الصدر ويمده نوراً؛ أن يستحدث الناس معاملات تسهل عيشهم، وتوفر أوقاتهم، وتمنحهم الكسب بأريحية، ولكن تبقى أي معاملة اقتصادية مالية تجارية، تخضع ابتداء وانتهاء؛ لضوابط شرعية، وضوابط اقتصادية. ومن هنا كثر السؤال عن التسويق الشبكي؛ لما نزل به من مستجدات تدعوا جميع الباحثين بشتى تخصصاتهم؛ سواء الجانب الشرعي، أو الجانب الاقتصادي؛ لضرورة البحث فيه، وبيان أحكامه الفقهية وانعكاساته الاقتصادية على الأفراد والدول، وتمييز موقعه من السوق التجارية، فجاء هذا البحث ليسلط الضوء على هذه المسألة من جانبين: الأول: بيان حكمه الشرعي، والثاني: بيان أثره على الاقتصاد
This research is tagged with: "Network Marketing, its jurisprudence and its economic effects on individuals and countries". Due to becoming famous among all members of our society, especially the youth; because it fills the soul pleased, and explains the chest and light it; to create people to facilitate the transactions of living, and does not consume their time, and give them a profit, but the survival of any commercial financial transaction, As well as the economic rules of the end, and hence the question of network marketing is incresing, because of the latest developments that call upon all researchers in all their fields of expertise, both the religious aspect and the economic aspect, for the need to research it and to explain its jurisprudence and its economic repercussions on individuals and countries, And a statement of its position from the market. This research came to shed light on this issue from two aspects: the first: the statement of its religious ruling, and the second: the statement of its impact on the economy
Keywords: الفقه الإسلامي -- فقه المعاملات -- الأحكام الفقهية -- التسويق الشبكي